SISTEM REKOMENDASI: BUKU ONLINE DENGAN METODE COLLABORATIVE FILTERING - Irfan, Mohammad; Cahyani, Andharini Dwi; R, Fika Hastarita (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
The book is a source of information regarding all aspects of life, especially education. However, low interest in reading among the public is a major issue in education today. Recommendation systems can help recommend the reader to more easily obtain information about the books to be read. Therefore, in this study made an online book recommendation system using Collaborative Filtering. Collaborative Filtering is one of the methods that can be used in making the recommendation system. The results of this study showed that the average value of the MAE (Mean Absolute Error) on trial 1 (1.064) is smaller than 2 trials (1.21), 4 trials (2,474) and test 5 (3.526). This shows that the more the amount of data used and if there is a user who has never rate a, then the resulting system is relatively inaccurate and generate recommendations if using Collaborative Filtering bad.